Achieveing the Implementation of Strategic Human Resource Management Practices: a review of the International scientific articles - Muhammad Tito Andrianto; Martinus Tukiran; Erna Herlina; Hermansyah Hermansyah; Junengsih Junengsih (Budapest International Research and Critics University, 2022)
The present paper critiques and analyses three articles ‘Measuring Employee Expectations in a Strategic Human Resource Management Research: Job Satisfaction’ which appeared in the journal ‘Procedia Social and Behavioral Sciences’, published in 2011, ‘Shattered but smiling: Human resource management and the wellbeing of hotel employees during COVID-19’ which appeared in the journal ‘International Journal of Hospitality Management’, published in 2021, and ‘Innovation Culture and Strategic Human Resource Management in Public and Private Sector within The Framework Of Employee Ownership’ which appeared in the journal ‘Procedia Social and Behavioral Sciences’, published in 2015. This review will begin by summarising the articles. It will then briefly analyse the effectiveness of the article based on how it was structured – investigating how the information is set out and whether the readers can access it effectively and with ease. And finally the article will be critiqued based upon its authority and accuracy, and how current and relevant the information presented is. The review will also analyse any graphs and tables before finally judging the article’s accessibility and credibility. The central theme of the paper is to present a ‘conceptual framework encompassing a range of organization's overall issues relevant to strategic human resource management’. The framework provides a foundation for organising the existing and the growing literature on international competition and ‘creating a map of the field’. The chosen articles can be used for both teaching and future research, but more importantly they are most beneficial for manager of multinational corporation. Which is aimed at providing then with ‘relating and synthesizing the different perspectives and prescriptions that are currently available for global strategic management’.